Communications in Interference Limited Networks - Utschick, Wolfgang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers means to handle interference as a central problem of operating wireless networks. It investigates centralized and decentralized methods to avoid and handle interference as well as approaches that resolve interference constructively. The latter type of approach tries to solve the joint detection and estimation problem of several data streams that share a common medium. In fact, an exciting insight into the operation of networks is that it may be beneficial, in terms of an overall throughput, to actively create and manage interference. Thus, when handled properly, "mixing" of data in networks becomes a useful tool of operation rather than the nuisance as which it has been treated traditionally. With the development of mobile, robust, ubiquitous, reliable and instantaneous communication being a driving and enabling factor of an information centric economy, the understanding, mitigation and exploitation of interference in networks must be seen as a centrally important task.
From the Contents: Interference-Aware Analog Computation in Wireless Networks -- Multicast in Networks of Broadcast Channels -- Random Medium Access for Multicast in Coded Wireless Packet Networks -- Arbitrarily Varying Channels.
Keywords: Telecommunication; Application software; Signal processing; Communications Engineering, Networks; Computer and Information Systems Applications; Signal, Speech and Image Processing